Deep learning model for glioma, meningioma, and pituitary classification - Toqa A. Sadoon; Mohammed H. Ali (Institute of Advanced Engineering and Science, 2021)
One of the common causes of death is a brain tumor. Because of the above mentioned, early detection of a brain tumor is critical for faster treatment, and therefore there are many techniques used to visualize a brain tumor. One of these techniques is magnetic resonance imaging (MRI). On the other hand, machine learning, deep learning, and convolutional neural network (CNN) are the state of art technologies in recent years used in solving many medical image-related problems such as classification. In this research, three types of brain tumors were classified using magnetic resonance imaging namely glioma, meningioma, and pituitary gland on the based of CNN. The dataset used in this work includes 233 patients for a total of 3,064 contrast-enhanced T1 images. In this paper, a comparison is presented between the presented model and other models to demonstrate the superiority of our model over the others. Moreover, the difference in outcome between pre- and post-data pre-processing and augmentation was discussed. The highest accuracy metrics extracted from confusion matrices are a precision of 99.1% for the pituitary, a sensitivity of 98.7% for glioma, a specificity of 99.1%, and an accuracy of 99.1% for the pituitary. The overall accuracy obtained is 96.1%.